Nicola Lake sheet [topographic] - Aitken, G. G. (George Griffiths), 1885-1955 (British Columbia Department of Lands, 1927)
This is a topographic map of Lake Nicola area in 1927 showing surveyed lands, First nations reserves, land districts, forest reserves, mining divisions, railways, telegraph, telephone and power lines, irrigation canals, roads, trails, rivers, lakes, rapids, bridges, cities and towns. Inset: Key map [regional map] Scale 1:126,720, or 2 miles to 1 inch. Relief shown by contours and spot heights. Shows surveyed lands, First nations reserves, land districts, forest reserves, mining divisions, railways, telegraph, telephone and power lines, irrigation canals, roads, trails, rivers, lakes, rapids, bridges, cities and towns. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .